2022
DOI: 10.3390/rs14051256
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Classification and Change Detection Methods of Drylands in Arid and Semi-Arid Regions

Abstract: The aim of this study was to clarify the distribution of irrigated drylands in arid and semi-arid areas, where complex terrain, diverse crops and staggered cultivated lands exist. This paper studied the classification methods of irrigated drylands based on temperature, precipitation, Normalized Difference Vegetation Index (NDVI) and Normalized Difference Water Index (NDWI) from Landsat data in the one-harvest area of the northern Loess Plateau of China by using the Google Earth Engine (GEE) platform. An extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…On the contrary, in dryland agriculture, frequent droughts cause precipitation to fall short of demand, coupled with the limitation of crop planting and growth period change, resulting in a smaller PUE in drylands compared with paddy fields. However, during the 13th Five‐Year Plan period, with the development of dryland agricultural science and technology, the PUE of drylands has been greatly improved (Xiao et al, 2023; Zhu et al, 2022). Woodlands is located in humid areas with abundant precipitation, and most of them are tree vegetation with large continuous area and high degree of depression, with strong photosynthesis, which dissipates a large amount of water, so the PUE shows a high level (Sancho‐Knapik et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, in dryland agriculture, frequent droughts cause precipitation to fall short of demand, coupled with the limitation of crop planting and growth period change, resulting in a smaller PUE in drylands compared with paddy fields. However, during the 13th Five‐Year Plan period, with the development of dryland agricultural science and technology, the PUE of drylands has been greatly improved (Xiao et al, 2023; Zhu et al, 2022). Woodlands is located in humid areas with abundant precipitation, and most of them are tree vegetation with large continuous area and high degree of depression, with strong photosynthesis, which dissipates a large amount of water, so the PUE shows a high level (Sancho‐Knapik et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Training and validation data were randomly selected across each of the images over the areas of interest (AOIs). Random sampling is extensively used for landuse/landcover mapping, as reported in the literature [12,[62][63][64][65][66][67]. We obtained 282 labels for randomized pixels in the AOIs.…”
Section: Classification Scheme and Sampling For Ground Truthingmentioning
confidence: 99%
“…A change matrix depicting changes in mine areas and non-mine areas from the initial analysis year (2005) to the final year of analysis (2020) was computed from the classified maps. To quantify spatiotemporal changes [64,81,82], we generated maps of gains and losses of mine and non-mine cover. Further, change detection statistics were used to compile a detailed tabulation of changes between images acquired during the study period.…”
Section: Change Detectionmentioning
confidence: 99%
“…Existing work focused on the application of traditional shallow machine learning algorithms combined with medium-resolution data to identify dryland land cover [34,35]. For instance, Zhu et al [36] obtained satisfactory classification results by integrating meteorological data and vegetation indices derived from Landsat imagery to detect irrigated dryland distribution changes using a random forest classifier. Likewise, Weng et al [37] identified typical landscapes, such as deserts, oasis, Gobi, and water systems, at an acceptable level based on the spectral information of HJ-1A/1 B imagery and an improved gcForest algorithm.…”
Section: Introductionmentioning
confidence: 99%